Analyzing Anna Foxx’s Character Development in A.J Finn’s The Woman in the Window - Jeinni Indrani Elizabeht Mangar; Adeline Grace M. Litaay (Austronesian: Journal of Language Science & Literature, 2025)
Character development in literature refers to the ability to provide a character with personality, depth, and motivation that propels them through a story. As an individual gains knowledge from previous experiences, a person who has overcome difficulties and problems in life will be stronger and become a better person. The study explores Anna Fox’s character development in The Woman in the Window. This research aims to describe the character development of Anna Fox in A.J. Finn’s novel and to examine the causes and effects of her development. The analysis uses a qualitative descriptive method, and the intrinsic approach is employed in this research. All data in this study collected The Woman in the Window by focusing on the main character of the story. The results of this study show three major aspects of Anna Fox’s character development: coping with fear and anxiety, overcoming drug and alcohol dependence, and managing loneliness and panic attacks. The causes of Anna Fox’s development are rooted in her friendship with Jane and Ethan Russell, as well as her experience of witnessing Jane Russell’s murder. Finally, the effect of Anna’s character development is that she is eventually able to live more normally and build genuine friendships, while others come to realize that she is not insane and apologize to her. In the end, Anna resumes her life as before by returning to her profession as a child psychologist.